The Effect of Electric Current in Hard Chrome Plating Process on the Corrosion Rate of SS400 Low Carbon Steel Plate for Warships - Firdauz, Mohammed Fat'han; Ananda, Dea Dwi; Kurniadi, Tedi (MUNISI: Military Mathematics and Natural Sciences, 2025)
Hard chrome plating is a technique used to protect metal from the effects of corrosion caused by the surrounding environment. The basic principle of the hard chrome plating process on metal is the reduction of chrome ions, resulting in chrome deposition on the cathode, following the principle of electrolysis. Electric current is one factor determining the quality of electroplating results. The immersion test is a correction factor for electroplating results to obtain corrosion rate values. This research used an experimental method involving one independent variable: electric current with current variations of 1 A, 2 A, 3 A, 4 A, 5 A, and 1 sample without chrome coating. In contrast, the dependent variable observed was the corrosion rate resulting from hard chrome plating. And without hard chrome plating. The controlled variable in this study was the length of soaking time for 7 days. The corrosive solution used is sodium chloride (NaCl), with a concentration of 3.5%. The research results show that the electric current resulting from hard chrome plating on SS400 steel significantly affects the results of the immersion test or corrosion rate test.